Pengaruh Kompensasi, Disiplin Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja pada PT. Telkom Akses Semarang - Ilham Arif Wicaksono; Haryani Haryani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study was to analyze the effect of compensation, work discipline and work environment on job satisfaction at PT Telkom Akses Semarang. The population in this study were all employees of PT Telkom Akses Semarang, totaling 73 people. Sample / respondents taken as many as 73 respondents, by measuring the census technique. The results showed that the compensation hypothesis test had a positive and significant effect on job satisfaction (t count = 3.225> t table = 1.671 with a significance figure = 0.002 < α = 0.05 (significant). Thus, the hypothesis (H1) that compensation has a positive effect on job satisfaction is proven. Work discipline has a positive and significant effect on job satisfaction (t count = 3.182> t table = 1.671 with a significance number = 0.002 < α = 0.05 (significant). Thus, the hypothesis (H2) that work discipline has a positive effect on job satisfaction is proven. The work environment has a positive and significant effect on job satisfaction (t count 5.645> t table = 1.671 with a significance number = 0.000 < α = 0.05 (significant). Thus, the hypothesis (H3) that the work environment has a positive effect on job satisfaction is proven. The regression coefficient β1 = 0.284 (positive sign) means that the greater the compensation received, the greater the job satisfaction. The regression coefficient β2 = 0.277, (positive sign) means that the more work discipline, the higher job satisfaction. Regression coefficient β3 = of 0.476 (positive sign) means that the more comfortable the work environment, the higher the job satisfaction at PT Telkom Access Semarang.